A Case Report of Melanoma as Acute Mastoiditis in a 10-Month-Old Female Child - Konstantina Chrysouli; Michael Tsakanikos; Sofia Stamataki (Case Reports in Otolaryngology)
We present a rare case of transplacental-transmitted maternal melanoma to the placenta and foetus during the pregnancy of a 34-year-old woman. She was diagnosed with a melanoma at the age of 25, for which she was treated with chemotherapy. During her pregnancy, she presented with a recurrence of the disease and died 3 months after delivery. The 10-month-old female child presented with a recurrent retroauricular oedema on the left side. A trephination of mastoid apophysis followed. Multiple fragments of dark-coloured tissue were sent for histological examination, and the immunophenotype showed a melanocytic tumour in the mastoid. A full radiological assessment showed no sign of metastasis. The child remained without treatment. Complete remission of bone metastatic lesion has been confirmed by follow-up; now, the child is 4 years old, alive, and without evidence of disease.